Case Report: A novel KNCH2 variant-induced fetal heart block and the advantages of fetal genomic sequencing in prenatal long-term dexamethasone exposure - Huang, Huiping; Jing, Siyuan; Wu, Shaoying; Wei, Li; Zhang, Qian; Hua, Yimin; Li, Yifei; Yu, Haiyan; Zhou, Kaiyu (Frontiers in Genetics, 2022)
Background: Fetal bradycardia is a common but severe condition. In addition to autoimmune mediated fetal heart block, several types of channelopathies induce high degree atrioventricular block (AVB). Long QT syndrome (LQTS) is a major causes of non-autoimmune-mediated fetal heart block. Due to the limitations of prenatal diagnostic technologies, LQTS is seldom identified unless fetal genetic screening is performed. Thus, long term prenatal dexamethasone (DEX) exposure becomes a challenge for these patients. Herein, we report a rare case of a novel KCNH2 variant related to LQTS and associated with high degree fetal AVB with long term DEX exposure. This case led us to review our prenatal administration strategy for such patients. Case Presentation: A fetus was identified as having a high degree AVB (2:1 transduction at 28+2 gestational weeks). Tests of immune function in pregnant women were conducted, including tests for thyroid function, rheumatic screening, autoimmune antibodies (such as anti-Ro/SSA and anti-La/SSB) and anti-nuclear antibodies (anti-ANA). Following the recommended protocol, the pregnant patient received DEX (0.75 mg/day) during pregnancy. Subsequently, the fetal AVB changed from 2:1 to prolonged AV intervals with ventricular tachycardia, suggesting a therapeutic benefit of DEX in some respects. However, a high degree AVB with a significantly prolonged QTc interval was identified in the neonate following birth. Genetic testing revealed a KCNH2 c.1868C>A variant induced LQTS. The body length remained approximately -3.2 SD from the reference value after prenatal long term DEX exposure, indicating a developmental restriction. Additionally, the functional validation experiments had been performed to demonstrate the prolonged duration of calcium transit both in depolarization and repolarization with KCNH2 c.1868C>A variant. Conclusions: Genetic screening should be recommended in fetuses with autoimmune antibody negative high degree AVB, especially for 2:1 transduction AVB and in fetuses with changes in fetal heart rhythm following initial DEX treatment. Genetic screening may help identify genetic variant–related channelopathies and avoid unexpected prenatal exposure of DEX and its possible long-term adverse complications postnatally.